Risk on-risk off: A regime switching model for active portfolio management - José P. Dapena; Juan Andrés Serur; Julián R. Siri (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2019)
Unlike passive management, where investors almost do not buy and sell securities, active management involves a set of trading rules that govern investment decisions regarding mainly market timing. In this paper, we take the basics of active management and the two fund separation approach, to exploit the fact that an investor can switch between the market portfolio and the risk free asset according to the perceived state of the nature. Our purpose is to evaluate if there is an active management premium by testing performance with our own non-conventional multifactor model, constructed with a Hidden Markov Model which depending on the market states signaled by the level of volatility spread. We have documented that effectively, there is present a premium for actively manage the strategies, giving evidence against the idea that "active managers" destroy capital. We then propose the volatility spread as the active management factor into the Carhart's model used to evaluate trading strategies with respect to a benchmark portfolio.
Keywords: C1; C3; N2; G11; 330; Regime switching; active investment; two fund separation; excess returns; hidden markov model; VIX